2019
DOI: 10.1038/s41598-019-51951-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole mitochondrial genome sequencing highlights mitochondrial impact in gastric cancer

Abstract: Mitochondria are organelles that perform major roles in cellular operation. Thus, alterations in mitochondrial genome (mtGenome) may lead to mitochondrial dysfunction and cellular deregulation, influencing carcinogenesis. Gastric cancer (GC) is one of the most incident and mortal types of cancer in Brazil, particularly in the Amazon region. Here, we sequenced and compared the whole mtGenome extracted from FFPE tissue samples of GC patients (tumor and internal control – IC) and cancer-free individuals (external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Mitochondria are organelles that perform major roles in cellular operation. Therefore, alterations in mitochondrial genome may lead to mitochondrial dysfunction and cellular deregulation, influencing carcinogenesis [ 45 ]. A recent study indicated that ZCCHC4 is a new human N(6)-methyladenosine methyltransferase, and knockout of ZCCHC4 eliminates the N(6)-methyladenosine modification on 28S rRNA, thereby reducing overall translation activity, which contributes to inhibiting liver cancer cells proliferation and reducing liver tumor size [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are organelles that perform major roles in cellular operation. Therefore, alterations in mitochondrial genome may lead to mitochondrial dysfunction and cellular deregulation, influencing carcinogenesis [ 45 ]. A recent study indicated that ZCCHC4 is a new human N(6)-methyladenosine methyltransferase, and knockout of ZCCHC4 eliminates the N(6)-methyladenosine modification on 28S rRNA, thereby reducing overall translation activity, which contributes to inhibiting liver cancer cells proliferation and reducing liver tumor size [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…All found variants were distributed in 11 mitochondrial regions: MT-RNR1 (1438), MT-RNR2 (2706), T-ND1 (3594 and 3666), MT-CO1 (7028), MT-ATP6 (8584), MT-CO3 (9545), MT-ND4 (10810, 10873, 11719 and 11914), MT-ND5 (12705, 13650 and 13789), MT-ND6 (14178 and 14560), MT-CYB (15043) and D-loop (73, 489, 16093, 16111, 16129, 16189, 16223, 16278, 16311, 16327, 16360, 16519 and 16527). It is noteworthy that 11 of these variants were exclusive to tumours (somatic) in the study by [ 6 ] and distributed in four regions: D-loop (73, 489, 16093, 16189 and 16360), MT-ND1 (3594 and 3666), MT-ND4 (10810 and 10873), and MT-ND5 (13650 and 13789). Regardless, from the total of 30 variants, the most frequent variants in GC were 11719 and 16223 (present in 12 individuals each), while the most frequent in TCMA was 11914 (15 individuals).…”
Section: Resultsmentioning
confidence: 96%
“…After dataset merging, we observed 90 individuals and 22 cancer types from TCMA that presented shared variants with GC. This was probably a reflection of different genetic ancestries in both datasets, considering that the GC dataset consisted of individuals from the Brazilian Amazon region, in which Native American mtDNA haplogroups are frequently found [ 6 ], while the TCMA dataset does not seem to include the Brazilian population. This emphasizes the importance of considering the genetic background of the studied populations and stresses the potential of the shared mutations observed in this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutserve is a local version of the scalable web server “mtDNA-server,” which was released in 2016 ( Weissensteiner et al, 2016 ). It has been used in variant identification studies for diseases like congenital lactic acidosis and gastric cancer ( Bravo-Alonso et al, 2019 ; Cavalcante et al, 2019 ). Mutserve performs internal quality control by excluding mitochondrial hotspots and sites with <10 reads and estimates a strand bias, as it handles forward and reverse reads separately.…”
Section: Methodsmentioning
confidence: 99%